Improvement of quality characteristics of peanut milk - Encarnacion, Sylvia S. (1981)
ABSTRACT To improve peanut milk quality characteristics, the effect of soaking peanuts in varying levels of NaHCO₃ and adding different stabilizers and flavors to the resulting peanut milk were determined. Subjecting peanuts to soaking for 12 hours at 21°-25°C in a 1.5% NaHCO₃ solution increased protein content and improved odor, flavor, and acceptability scores of peanut milk significantly from the control. Percentage protein dispersibility test of milk samples containing 0.1% CMC; 0.1% carageenan; 0.1% xantham gum, with and without 0.1% K₂HPO₄ revealed that the addition of K₂HPO₄ did not improve peanut milk stability. These tests also indicted that the xantham gum had the best stabilizing ability. Sensory evaluation results showed that further increase in concentration of xantham gum form 0.1% to 0.2% resulted in significantly better acceptability scores. Addition of 0.15% milk caramel, chocolate, and strawberry flavors to peanut milk did not improve its acceptability. Average acceptability scores, in the case of chocolate and strawberry flavored peanut milk, were even lowered.